Autocorrelation and Heteroscedasticity in Regression Analysis - Kumar, Nand Kishor (Journal of Business and Social Sciences, 2023)
In the world of econometrics and time series analysis, autocorrelation and heteroscedasticity are two statistical issues that analysts often encounter when modeling data. Both phenomena can seriously undermine the reliability of regression results if left untreated, leading to biased conclusions and faulty predictions. Autocorrelation and heteroscedasticity are important considerations in any regression analysis, especially when explaining with time series analysis. Both phenomena undermine the accuracy of the model if left unaddressed. By applying the appropriate tests and corrective measures, such as Generalized Least Squares or robust standard errors, analysts can ensure that their models remain reliable, leading to more valid inferences and better decision-making. In practice, detecting and correcting for it should be a standard part of the model validation process to avoid incorrect conclusions and improve the robustness of the results.